2022
DOI: 10.1127/entomologia/2022/1365
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between integrated pest management, pollinator introduction, and landscape context on avocado Persea americana productivity

Abstract: Pest management and insect pollination are important services that support crop production but are most often studied in isolation in cropping systems. Avocado Persea americana Mill. is an economically important crop in East Africa, which suffers from pest threats and potential drawbacks of the global pollinator crisis. The integration of pest and pollinator management is a growing research trend as a potential solution for sustainable crop production with minimum adverse effects on the environment and biodive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
5
2
Order By: Relevance
“…In the first season, there was no effect of the treatments on the daily catches of Z. cucurbitae , while in the second season, Z. cucurbitae catches were higher in farms with no PS than in farms with PS, implying that the presence of stingless bee colonies did not increase the abundance of Z. cucurbitae . Contrary to our study, Toukem et al (2022) reported an increase in B. dorsalis catches on avocado farms with honeybee colonies, which was attributed to the smell of honey sugar and fermentation of beebread, which attracted fruit flies (Lee et al 2015). Furthermore, in the second season, Z. cucurbitae catches were highest in control farms across low NDVI, presumably due to fewer natural enemies (Copeland et al 2006) and as reported by Mwatawala et al (2006) for Tanzanian lowland regions.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In the first season, there was no effect of the treatments on the daily catches of Z. cucurbitae , while in the second season, Z. cucurbitae catches were higher in farms with no PS than in farms with PS, implying that the presence of stingless bee colonies did not increase the abundance of Z. cucurbitae . Contrary to our study, Toukem et al (2022) reported an increase in B. dorsalis catches on avocado farms with honeybee colonies, which was attributed to the smell of honey sugar and fermentation of beebread, which attracted fruit flies (Lee et al 2015). Furthermore, in the second season, Z. cucurbitae catches were highest in control farms across low NDVI, presumably due to fewer natural enemies (Copeland et al 2006) and as reported by Mwatawala et al (2006) for Tanzanian lowland regions.…”
Section: Discussioncontrasting
confidence: 99%
“…We found the lowest daily catches of Z. cucurbitae in IPPM farms in medium NDVI, but only during the second season, illustrating a synergistic effect. Unlike in our study, Toukem et al (2022) reported no synergistic effect of IPM and PS in reduction of Tephritid fruit fly densities in avocado production systems, however, independently, IPM reduced fruit fly pest abundance. Findings from our study reported a main effect of NDVI on the catches of D. bivittatus , with the highest catches observed across low NDVI.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations